Elliot Snow papers - Snow, Elliot, 1866-1939.; Fox, Josiah, 1763-1847.; Smith, Horatio Davis, 1845-1918.
Correspondence, logbooks, journal, speech, writings, articles, notebooks, newspaper clippings, printed matter, scrapbooks, blueprints, specifications, photographs, and other papers relating to the history and restoration of the USF Constitution. Correspondents include William Alcott, Philip Andrews, George A. Bahn, James Barnes, Jouett Taylor Cannon, Henry T. Claus, William E. Foster, Letitia A. Humphreys, Constance Lathrop, Paul C. Nicholson, Haviland Hull Platt, Albert Sydney Snow, William F. Spicer, Karl Vogel, and Curtis Dwight Wilbur.
Includes correspondence and other papers of Josiah Fox relating primarily to naval construction. Fox's correspondents include John Cassin, John Cock, Peter Gardner, William Hall, Jonathan Hopkins, and Henry L. Langdon. Also includes correspondence, logbook, writings, notebooks, scrapbooks, and other papers of Horatio Davis Smith relating chiefly to the U.S. Revenue-Cutter Service. Correspondents include Francis Martin, John McGowan, George Henry Preble, and Sidney D. Shattuck.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Alcott, William -- Correspondence; Andrews, Philip, -- 1866-1945 -- Correspondence; Bahn, George A. -- Correspondence; Barnes, James, -- 1866-1936 -- Correspondence; Cannon, Jouett Taylor, -- 1865-1949 -- Correspondence; Cassin, John, -- 1758-1822 -- Correspondence; Claus, Henry T. -- Correspondence; Foster, William E. -- 1851-1930 -- Correspondence; Humphreys, Letitia A. -- Correspondence; Lathrop, Constance -- Correspondence; Nicholson, Paul C. -- 1888-1956 -- Correspondence; Platt, Haviland Hull, -- 1889- -- Correspondence; Preble, George Henry, -- 1816-1885 -- Correspondence; Snow, Albert Sydney, -- 1845-1932 -- Correspondence; Spicer, William F. -- Correspondence; Vogel, Karl -- Correspondence; Wilbur, Curtis Dwight, -- 1867-1954 -- Correspondence; United States. -- Navy; United States. -- Revenue-Cutter Service; Constitution (Frigate); Shipbuilding -- United States; Warships; Naval officers